1995
DOI: 10.1096/fasebj.9.10.7615163
|View full text |Cite
|
Sign up to set email alerts
|

The cell biology of the plasminogen system

Abstract: The plasminogen system plays a pivotal role in maintaining vascular patency and in cell migration. Binding of plasminogen to surfaces (i.e., fibrin or cells) is of crucial importance in regulating the function of this system. Plasmin(ogen) binds to cells with low affinity and high capacity via its lysine binding sites, which are associated with its kringle domains and recognize carboxy-terminal lysines of cell surface proteins. Upon binding to cellular receptors, plasminogen is more readily activated; bound pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
332
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(343 citation statements)
references
References 52 publications
11
332
0
Order By: Relevance
“…[26][27][28][29][30][31][32][33] Independent studies also have implicated externalized α-enolase and GAPDH on mammalian and pathogen surfaces as sites for plasminogen binding and subsequent activation by host or pathogen activities, [26][27][28]30,31,[34][35][36] and we have demonstrated that externalized glycolytic enzymes on the apoptotic cell surface, including α-enolase, also are sites for plasminogen binding. 12 Although enhanced virulence has been attributed to the presumptive augmentation in mobility through matrix or fibrin clots associated with localized plasminogen activation following binding on the pathogen surface, 37,38 no compelling physiological rationale exists for plasminogen binding on non-invasive bacteria and apoptotic cells.…”
Section: Box 1 the Repertoire Of Innate Apoptotic Immunity Early Transupporting
confidence: 58%
“…[26][27][28][29][30][31][32][33] Independent studies also have implicated externalized α-enolase and GAPDH on mammalian and pathogen surfaces as sites for plasminogen binding and subsequent activation by host or pathogen activities, [26][27][28]30,31,[34][35][36] and we have demonstrated that externalized glycolytic enzymes on the apoptotic cell surface, including α-enolase, also are sites for plasminogen binding. 12 Although enhanced virulence has been attributed to the presumptive augmentation in mobility through matrix or fibrin clots associated with localized plasminogen activation following binding on the pathogen surface, 37,38 no compelling physiological rationale exists for plasminogen binding on non-invasive bacteria and apoptotic cells.…”
Section: Box 1 the Repertoire Of Innate Apoptotic Immunity Early Transupporting
confidence: 58%
“…Plasminogen is a proenzyme found in plasma and extracellular fluids, which is converted to the broad spectrum serine protease plasmin upon activation (46). Active plasmin is capable of degrading fibronectin, fibrin, vitronectin, and laminin, with considerable evidence for the ability of plasmin to facilitate extracellular matrix degradation and invasion (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, ligated plasmin can still be inactivated by aprotinin, which competes with fibrin for the plasmin active site. There is a growing list of ubiquitous plasminogen receptors, including alpha-enolase, cytokeratin 8, and annexin 11 [36]. Plasmin displays a broad spectrum activity, and is able to degrade many glycoproteins (laminin, fibronectin) and proteoglycans of the ECM, as well as fibrin, and to activate other proteinases such as pro-metalloproteinases (MMP-1, MMP-3 and MMP-9).…”
Section: The Plasminogen Systemmentioning
confidence: 99%